1991
DOI: 10.1073/pnas.88.22.10064
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of holo 3 alpha,20 beta-hydroxysteroid dehydrogenase: a member of a short-chain dehydrogenase family.

Abstract: The x-ray structure of a short-chain dehydrogenase, the bacterial holo 3a,20/3-hydroxysteroid dehydrogenase (EC 1.1.1.53), is described at 2.6 A resolution. This enzyme is active as a tetramer and crystallizes with four identical subunits in the asymmetric unit. It has the a/( fold characteristic ofthe dinucleotide binding region. The fold of the rest of the subunit, the quarternary structure, and the nature of the cofactor-enzyme interactions are, however, significantly different from those observed in the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
188
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(194 citation statements)
references
References 31 publications
5
188
0
1
Order By: Relevance
“…Following the three-dimensional structure of the homologous region in the 3a,20/3-hydroxysteroid dehydrogenase, these two glycines are clearly positioned on the outer surface of the molecule, at the hinge of an a-j? connecting segment [5]. According to these data, both could be crucial for the spatial configuration of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the three-dimensional structure of the homologous region in the 3a,20/3-hydroxysteroid dehydrogenase, these two glycines are clearly positioned on the outer surface of the molecule, at the hinge of an a-j? connecting segment [5]. According to these data, both could be crucial for the spatial configuration of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Lys15'j is invariably present in ADH of 36 species of Drosophila and also in all analyzed members of the short-chain family. The high degree of conservation, the proximity to the catalytic Tyr and the chemical features of its side chain clearly suggested that this Lys could well be enclosed in the catalytic cleft [5], providing an alkaline environment for catalysis. Its E-NH, group, if suitably located with respect to Tyr, could have the effect of lowering the apparent pK, of the phenolic group, thus facilitating the hydride transfer reaction at much lower, physiological pH.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, residue identities between the different enzymes are 20±30%, indicating early deviation from a common origin. Nevertheless, crystallographic analysis of so far two bacterial [9,13] and three mammalian enzymes [10±12] has revealed the same Rossmann fold secondary structure and a highly conserved three-dimensional architecture. By combining primary and tertiary structural information it has been possible to identify several sequence motifs that are conserved in most SDRs.…”
Section: Discussionmentioning
confidence: 99%
“…The functional role of the reactive cysteine, however, remains speculative. Based on the known tertiary structure of the bacterial 3a/20b-hydroxysteroid dehydrogenase [9], Jo Èrnvall and colleagues have constructed a three-dimensional model of human carbonyl reductase [25]. Although the model has some uncertainties, particularly in the C-terminal part of the peptide chain, it clearly identifies the residues constituting the a-helices and b-pleated sheets of the Rossmann fold and positions Cys227 in the C-terminal part of the bF strand, where it precedes a highly conserved proline residue.…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminus of the molecule is shown in blue, and the C-terminus in yellow. The nomenclature for secondary structural elements was adapted from Ghosh et al 17 The missing region is depicted by a dashed magenta line. bind in an extended conformation to residues forming the base of the active cleft between the two domains.…”
Section: Oligomeric Assembly and Intersubunit Contactsmentioning
confidence: 99%